Building Sustainable Couples in International Relations
XIII, 255 p.
Keywords: The contributors investigate processes of international conflict transformation and peaceful cooperation. They highlight how critical intermediary-level components have proved more conducive to promoting rapprochement between rival states than interstate diplomatic engagement through incremental identity-change.